Impact of Loads Connected by Electrification Projects on the Electricity Distribution Network in Northern Benin - CHETANGNY, Patrice Koffi; ZOGBOCHI, Victor; HOUNDEDAKO, SOSSOU; BARBIER, Gérald; CHAMAGNE, Didier (My University, 2023)
The republic of Benin is experiencing low electrification rate especially in rural areas of the country. To address this issue, many projects are engaged to enlarge the actual distribution network. By so doing, the charge of the network increases enormously. The problem that arises immediately is how the network respond to the increase in load? And how is the stability of the network affected by the new MV lines constructed? This work aimed at modelling and simulating the northern part of the distribution network where PERU and EBID projects are ongoing. NEPLAN software is used to represent the network without new extension and by considering the new projects. The results show that the Northen MV network without extensions is already subjected to significant voltage drops. This is the case of the Natitingou substation where a voltage drops of up to 18% is recorded. In addition to these voltage drops, the existing North MV network is experiencing active and reactive power losses. By considering new loads created by the network extension, the voltage drop at the same substation of Natitingou increases to 22%. There are a severe active and reactive power losses estimated at 10 kW. These show that the network will be unstable if all the ongoing projects have ended. Therefore, preventive measures are necessary to be taken by integrating backup power sources from the local available renewable energy.
Keywords: Reactive power; Renewable energy sources; Analytical models; Substations; Distribution networks; Quality of service; Software